The Impact of Social Responsibility Costs on Financial Performance of Jordanian Banks - Awwad , Mohammad Suleiman; Al-Qaissi , Buthinah Aref (Jordan Journal of Business Administration, 2023)
This study aimed to investigate the impact of social responsibility costs on the financial performance of Jordanian banks. The study sample consisted of sixteen Jordanian commercial and Islamic banks listed in Amman Stock Exchange (ASE), using cross-sectional time-series data covering the years (2010-2017). Data was analyzed using fixed -and random- effect regression models using STATA 12.0. The study focused on three different dimensions of Jordanian banks' social responsibility (responsibility towards employees, responsibility towards products and customers and responsibility towards the local community) to determine their impact on the financial performance of Jordanian banks (return on assets, earnings per share and Tobin’s Q index). The results showed different effects of social responsibility dimensions on the financial performance of Jordanian banks. Overall, responsibility towards the social community was the most influential dimension on all financial-performance indicators, followed by responsibility towards employees which positively affects return on assets and earnings per share, while not having any impact on Tobin's Q index. Finally, responsibility towards products and customers showed a negative impact on return on assets, while not having any impact on the other performance indicators.